Hubungan Motivasi Belajar Dengan Prestasi Mahasiswa Mik Di Stikes Santa Elisabeth Medan - Beatrice Lumbanraja; Alejandro Arauz Julia (Jurnal Pendidikan dan Pembelajaran, 2022)
Education must be able to be moved in a directed manner, so that the implementation of education is able to keep up with increasingly advanced technological developments, and so that education can be carried out based on science which is very rapidly at this time, it is expected to be able to make humans with high quality. Methods: This study uses quantitative research methods using a cross-sectional design, where cross-sectional is used to determine the relationship between learning motivation and student achievement. This research data uses the chi-square test to see if there is a relationship between learning motivation and student achievement. The population in this study were all students of health information management from level 1 to level 4, totaling 47 students. Results: Based on the results of research conducted on the relationship between learning motivation and student achievement in Health Information Management at Stikes Santa Elisabeth Medan, it showed that the majority in the High Motivation category were 28 respondents (59.6%), and learning achievement was in the good category as many as 27. respondents (57.4%). The results of the chi-square analysis conducted on the relationship between learning motivation and learning achievement showed that from 47 respondents, the p-value = 0.001 (p value <0.05). Conclusion: The lower the motivation possessed by students, the lower the achievement obtained. Vice versa, the higher the motivation possessed by students, the higher the achievement obtained